2016
DOI: 10.1039/c5np00159e
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of diversity and stereochemical outcomes in the biosynthetic pathways of cyclobutane-centered marine alkaloid dimers

Abstract: Covering: up to 2016Dictazoles and sceptrins are singular metabolites of marine origin. The present dichotomic case study provides a comprehensive perspective on these cyclobutane-centered alkaloids and their respective families. Indeed, their upstream and downstream chemistry are both treated herein. Relevant isolation reports and bio-inspired total syntheses are used to decipher the currently admitted biosynthetic hypotheses as well as the emergence of diversity in the two series. This review proposes a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 141 publications
0
32
0
Order By: Relevance
“…In this context,aversatile and flexibles creening strategy to determine rapidlyt he right additives and to efficiently perform the photocycloaddition in av ery simple manner would be highly desirable, especially for cost-effective and large-scale production of structurally and biologically relevant cycloadducts [11] with well-defined regio-and stereochemistry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context,aversatile and flexibles creening strategy to determine rapidlyt he right additives and to efficiently perform the photocycloaddition in av ery simple manner would be highly desirable, especially for cost-effective and large-scale production of structurally and biologically relevant cycloadducts [11] with well-defined regio-and stereochemistry.…”
mentioning
confidence: 99%
“…Other carboxylic acids, such as higher analogues (malonic and succinic acids b-c,e ntries 3, 4, Ta ble 1), unsaturated acids (maleicand fumaricacids d-e,entries 5, 6, Table 1), benzeneoligocarboxylic acids f-k (entries 7-12, Ta ble 1) as well as simple monocarboxylic acid,such as phenylacetic acid l (entry 13), displayede ither lower efficiency( leadingt ol ower yields but the reaction mixtures remained rather clean, entries 3, 6, 7, 9, 10, Ta ble 1) or unsuitability as additive due to the formationo f complex mixtures of other isomeric adducts and unidentified side products (entries 4,5,8,(11)(12)(13)Ta ble 1).…”
mentioning
confidence: 99%
“…Hence,starting from three different natural aplysinopsinderived monomers,wewere able to access four cyclobutanecentered skeletons,i ncluding natural dictazole B. Interestingly,t he homodimer 2a could also be further converted to yet another natural product, tubastrindole B, through ar ingexpansion cascade involving the formation of Mancinis intermediate (Scheme 1), thus showcasing the possible generalization of this approach to the entire aplysinopsin family of natural products. [34] In summary,w ed eveloped an unprecedented DNAtemplated [2+ +2] photodimerization process and demonstrated its synthetic utility by applying it to the synthesis of spiro-fused cyclobutane-containing compounds including the natural heterodimer dictazole B. Thel atter was obtained in 16 %i solated yield, which significantly improved the results obtained under the standard solvent-free conditions.M oreover, by applying solid-state supramolecular principles ascertained by CD spectroscopy,w eh ave shown that DNAc ould be au seful template to build aggregates with photoreactive units.M ost importantly,w eb elieve that this method is not limited to the aplysinopsins.I ndeed, by fine-tuning the specific interaction between DNAa nd any given monomer, we should be able to extend the scope of the method and thus pave the way to new target-oriented syntheses.…”
Section: Angewandte Chemiementioning
confidence: 88%
“…Hence, starting from three different natural aplysinopsin-derived monomers, we were able to access four cyclobutane-centered skeletons, including natural dictazole B. Interestingly, the homodimer 2a could also be further converted to yet another natural product, tubastrindole B, through a ring-expansion cascade involving the formation of Mancini's intermediate (Scheme 1), thus showcasing the possible generalization of this approach to the entire aplysinopsin family of natural products. [34] In summary, we've developed an unprecedented DNA-templated [2+2] photodimerization process and demonstrated its synthetic utility by applying it to the synthesis of spiro-fused cyclobutane-containing compounds including the natural heterodimer dictazole B. The latter was obtained in 16% isolated yield, which significantly improved the results obtained under the standard solvent-free conditions.…”
Section: A Aplysinopsins Family: Dictazoles As Synthetic Gatewaysmentioning
confidence: 92%